Telegram - Albornoz, Alvaro de, b. 1879 ; Miaja Menant, José, 1878-1958 ; Díez-Canedo, Enrique, 1879-1944 ; Albar, Manuel ; Belausteguigoitia, Ramón de. ; Armendarez ; Alfarache Arrabal, Progreso ; Vargas ; Tomás Alvarez, Belarmino, 1887-1950; Martínez Barrio, Diego, 1883-1962
1942-11-18 013-0021-001 292/946/13/21(i)